Forns index as a useful noninvasive predictor of esophageal varices in liver cirrhosis - Siregar, Rizqi Arini; Dairi, Leonardo Basa; Siregar, Gontar Alamsyah (Universa Medicina, 2016)
BackgroundRupture and bleeding from esophageal varices are major complications of portal hypertension and associated with a high mortality rate. Non-invasive serum markers of liver fibrosis could be used as predictors of esophageal varices in cirrhotic patients. The objective of this study was to assess the performance of Forns index as a noninvasive predictor in diagnosing esophageal varices.MethodsA cross-sectional study was done in 51 cirrhotic patients who were admitted to Adam Malik hospital, Medan. Demographic and clinical data were recorded and laboratory tests were performed, so that Forns index could be calculated. The difference between Forns index and size of esophageal varices as determined by endoscopy was tested by independent-t and Mann-Whitney analysis. The diagnostic performance was assessed using sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), accuracy, likelihood ratios and areas under the receiver operating characteristic curves (AUROC). ResultsOf the 51 patients with esophageal varices included in this study, the size of esophageal varices comprised F2 (37.3%), F3 (33.3), and F1 (29.4%). Most patients were of Child-Plug C type (52.6%). There was a significant difference between Forns index and grade of esophageal varices. The AUROC for Forns index was 0.717 (95% CI: 0.561 - 0.872) and the cut-off >7.92 was highly predictive to diagnose large esophageal varices with a sensitivity of 63.9%, specificity of 73.3%, PPV of 85.2%, NPV of 45.8% and accuracy of 71.7%.ConclusionForns index was significantly increased in large esophageal varices. Forns index is a good noninvasive predictor of esophageal varices in cirrhotic patients.